(untitled) (Proceeding of International Conference on Islamic Economics, Islamic Banking, Zakah and Waqf, 2023)
The potential for the herbal business and Islamic medicine in Indonesia is enormous. Herbal medicine and Islamic medicinal treatment is an alternative medicine that can add to the world’s health treasures. However, this potential has not been utilized effectively by practitioners of Islamic medicinal treatment and herbal medicine businesses. One way that has not been used optimally is digital promotion. Even though promotion through digital has a great opportunity as long as it is done correctly and in accordance with market needs. This study aims to determine the effectiveness of digital in the development of herbal medicine and Islamic medicinal treatment businesses. This research is a field research with a qualitative method, in which the researcher assesses and then gives an assessment of the reality in the field using a descriptive approach. The results of this study indicate that digital is very effective in developing herbal medicine and Islamic medicinal treatment businesses. Among the factors that influence digital effectiveness are: personal branding, sweet lies/business actors with consumers, the intensity of promotion through social media, consumers’ need for Islamic medicinal treatment and herbal medicines and the amount of available promotional funds.